2017
DOI: 10.1002/adma.201701641
|View full text |Cite
|
Sign up to set email alerts
|

N‐Type Organic Thermoelectrics: Improved Power Factor by Tailoring Host–Dopant Miscibility

Abstract: In this contribution, for the first time, the polarity of fullerene derivatives is tailored to enhance the miscibility between the host and dopant molecules. A fullerene derivative with a hydrophilic triethylene glycol type side chain (PTEG-1) is used as the host and (4-(1,3-dimethyl-2,3-dihydro-1H-benzoimidazol-2-yl)phenyl)dimethylamine n-DMBI) as the dopant. Thereby, the doping efficiency can be greatly improved to around 18% (<1% for a nonpolar reference sample) with optimized electrical conductivity of 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
193
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(208 citation statements)
references
References 54 publications
14
193
1
Order By: Relevance
“…For the practical TE applications, both efficient p‐type and n‐type TE materials are required; however, the development of the latter lags much behind that of the former . For this reason, growing research efforts are being directed towards developing better n‐type TE materials . So far, advanced conjugated‐backbone designs targeting favorable energetics, high mobility, planar structure, and good host/dopant miscibility have been reported .…”
Section: Thermoelectric Properties Of Solution‐processed N‐type Conjumentioning
confidence: 99%
“…For the practical TE applications, both efficient p‐type and n‐type TE materials are required; however, the development of the latter lags much behind that of the former . For this reason, growing research efforts are being directed towards developing better n‐type TE materials . So far, advanced conjugated‐backbone designs targeting favorable energetics, high mobility, planar structure, and good host/dopant miscibility have been reported .…”
Section: Thermoelectric Properties Of Solution‐processed N‐type Conjumentioning
confidence: 99%
“…[14] Liu et al demonstrated a modified fullerene derivative, PTEG-1, that shows an increased miscibility at the nanoscale level and thereby achieved a PF of 16.7 µW m −1 K −2 with σ ≈ 205 S m −1 at 40 mol% of N-DMBI. [15] For p-type OTE, most reported experimental data seem to follow an empirical quasi-universal power law relationship between the Seebeck coefficient S and conductivity as S ∝ σ − 1/4 . [2,3] In view of the limited number of reported data, it is still unclear whether n-type OTE also follow this power law, and different power law slopes have been reported.…”
Section: High Seebeck Coefficient and Power Factor In N-type Organic mentioning
confidence: 99%
“…Gray and yellow dots indicate p-and n-type OSC, respectively; light yellow data are taken from refs. [11,12,15,28] and dark yellow from this work; for the latter, dots w/ and w/o red perimeter are for inverse-sequential doping and bulk doping, respectively; All p-type data come from our group. [23] Lines are model calculations with parameters: intersite distance a NN = 1.8 nm; Gaussian disorder σ DOS = 0.08 eV; temperature T = 300 K; inverse localization length α = 5 × 10 8 nm −1 .…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 2 more Smart Citations